Prevalence, Severity, and Functional Impairment of Premenstrual Syndrome Among Late Reproductive-Age Women in Rural Karnataka: A Cross-Sectional Study - Manjrekar, Shivani; Patil, Sandeep (National Journal of Community Medicine, 2025)
Background: Evidence on the burden of premenstrual syndrome (PMS) among late reproductive-age rural women in India is limited. To estimate PMS prevalence and severity, describe symptom and functional-impairment patterns, and examine associated predictors. Materials and methods: A cross-sectional study was conducted among women aged 35-45 years attending the outpatient department of a rural health training centre from January to June 2022 (n=270). The Premenstrual Symptoms Screening Tool (PSST) was forward-back-translated into Kannada and administered with demographic, menstrual, and behavioural variables. Results: PMS was reported by 90.0%; 62.2% had moderate-severe PMS (95% CI 56.3-67.8), 4.4% had severe PMS, and 27.8% had mild/sub-threshold PMS. Fatigue/lack of energy (98.4%), physical symptoms (95.9%), and difficulty concentrating (82.7%) were the most common symptoms. Functional impairment most often affected college/work productivity (84.0% moderate; 100.0% severe) and relationships with family (82.7% moderate). Significant predictors included regular cycles, earlier menarche, family history, lower physical activity, frequent sweet intake, and oral-contraceptive use (protective) (p<0.05). Conclusion: PMS burden and functional impairment are substantial. Routine screening and primary-care counselling are warranted along with the primordial need for increased awareness.